Pengaruh Susu Kedelai Edamame dan Pijat Oksitosin terhadap Peningkatan Produksi ASI: Effect Of Edamame Soy Milk and Oxytocin Massage on Increasing Breast Milk Production - Tyas, Trisna Pangestuning; Perbawati, Dinar (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Exclusive breastfeeding is the optimal source of nutrition for infants, providing balanced nutrients essential for growth and development. However, exclusive breastfeeding coverage in several regions remains below national targets. In Patrang District, Jember Regency, only 45.60% of infants aged 0–6 months received exclusive breastfeeding in 2021, far below the 80% target set for 2022. One contributing factor is the limited knowledge of postpartum mothers regarding breast care, which affects milk expression and production. This study aimed to determine the effectiveness of galactagogue intervention in the form of edamame soy milk and oxytocin massage in increasing breast milk production among postpartum mothers. This study employed an experimental research design with a two-group pretest–posttest approach. The respondents were postpartum mothers who met the inclusion criteria and were divided into two intervention groups: the oxytocin massage group and the edamame soy milk group. The independent variables were oxytocin massage and edamame soy milk consumption, while the dependent variable was breast milk production. Breast milk production was measured indirectly through changes in infant body weight before and after the interventions. Data were analyzed using the dependent t-test. The results showed a significant increase in breast milk production in both intervention groups. In the oxytocin massage group, there was a statistically significant difference between pretest and posttest measurements. Similarly, the edamame soy milk group demonstrated a significant increase in infant weight after the intervention, with a p-value of 0.000 (p < 0.05), indicating a significant effect on breast milk production. In conclusion, both oxytocin massage and edamame soy milk were effective in increasing breast milk production among postpartum mothers. These findings suggest that non-pharmacological interventions can be applied as supportive strategies to improve exclusive breastfeeding outcomes. Health workers are encouraged to incorporate breast care education and nutritional interventions into postpartum care to help increase exclusive breastfeeding rates.